(3QSGdI JaSjQ eG MhJg NjQ GdHQjI ef CSQGQ GdUfGYI GdWHjIs - (3GdSGfhSjs
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HGdbOje eNJQY GdhLhO ef GdYOe CeG HYO abO LQi Hjfi hHjf ENhGfi GdfLHGA cdGe ai aVd UfGYI GdWH hEfJgGA TWQ GdYde dbhdg Udi Gddg Ydjg hSde (B: (3GdYde YdeGf Yde GdCOjGf hYde GdCHOGf s
(3BNQgG (B:s
(3hjJgjC GdLSe dbHhd GdZPGA aEPG ONd GdZPGA bdJ GdMQGQI GdZRjRjI ajg aYdkG eMehO GdJbOe GdQjGVI Ydjg aJSJbje dPdc GdUMI HEPf Gddg JYGdi gPG eG CQOJ HKg ai gPg GdQSGdI GdejehfI hGdMeO ddg hMOg hUdi Gddg Ydi ef dGfHi HYOg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdWHs